Domino effects in the process industries : modeling, prevention, and managing - Reniers, Genserik L. L. (Amsterdam ; Boston ; Heidelberg ; London : Elsevier, 2013)
Annotation Domino Effects in the Process Industries discusses state-of-the-art theories, conceptual models, insights and practical issues surrounding large-scale knock-on accidents-so-called domino effects-in the chemical and process industries. The book treats such extremely low-frequency phenomena from a technological perspective, studying possible causes and introducing several approaches to assess and control the risks of these scenarios. The authors also examine these events from a managerial viewpoint, discussing single and multi-plant management insights and requirements to take pro-active measures to prevent such events. Academics, regulators, and industrialists who study and analyze domino effects in order to prevent such events will find the book unique and highly valuable. Outlines available methods in analyzing these events, aiding understanding of the accidents and their causesCovers current modelling, control and management tactics of domino effects, -facilitating preventionIdentifies areas where new research is needed.
Includes bibliographical references and index.
Keywords: Manufacturing processes; Chemical industry